The etiology of occupational pulmonary aluminosis - the past and the present - Smolkova, Petra; Nakladalova, Marie (Biomedical papers, 2014)
Background: The authors review pulmonary aluminosis caused by exposure to dust containing aluminium and its compounds, mainly oxides. Special attention is paid to various factors of occupational exposure as to an important etiologic issue. The condition has a rich and interesting history dating back to the 1930s. The most significant occupational exposures are associated with processes in bauxite smelting, the use of fine aluminium powder, exposure to aluminium welding fumes, grinding and polishing of aluminium materials.Methods and Results: A literature search for relevant scientific studies in English was performed using the following internet databases: relevant sections of The Cochrane Library, EBSCO Discovery Service, Ovid, ProQuest Science Journals, PubMed, ScienceDirect, Scopus and Web of Knowledge. The initial clinical manifestations of pulmonary aluminosis are exertional dyspnea with dry, non-productive cough. Depending on the type and length of the occupational exposure, ventilatory defects may vary considerably from restrictive to obstructive pattern. Radiographic findings commonly showing nodular or slightly irregular opacities are predominantly located in the upper, less frequently in the lower lung fields, or can have a diffuse pattern. In advanced stages, severe pulmonary fibrosis with honeycombing occured.Conclusions: Although pulmonary aluminosis is a very rare disease, it still occurs. Since the industrial importance and use of aluminium continue to rise, lung damage from exposure to respirable aluminium particles should not be overlooked but monitored and prevented. Even today, the pathophysiology of pulmonary aluminosis has not been explained as yet.
Keywords: pulmonary aluminosis; aluminium and its compounds; pneumoconiosis